KOMUNIKASI ANTARPRIBADI KONSELOR DENGAN ODHA (ORANG DENGAN HIV/AIDS) DALAM MEMOTIVASI HIDUP ODHA DI KLINIK VOLUNTARY COUNSELLING AND TESTING (VCT) KOTA DUMAI - Triani, Dini Dwi; Lubis, Evawani Elysa (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Currently HIV / AIDS has spread widely in almost all regions of the world includingIndonesia. Dumai city is one of the areas vulnerable to HIV / AIDS. During 2017, thenumber of HIV and AIDS cases was 598 cases. Patients with HIV / AIDS or so-called ODHA(People With HIV / AIDS), often experience psychological problems resulting from theillness and negative stigma from the surrounding environment. PLWHA requires counselorsto be able to change the behavior of PLWHA. The role of counselor at VCT ClinicPuskesmas Dumai Kota is very important in providing guidance, knowledge, behaviorchange, and motivate the life of PLWHA. Interpersonal communication is very important forcounselors and PLWHA in VCT Clinic. The purpose of this research is to know the stages ofcounseling HIV/AIDS, effectiveness of communication between counselor and PLWHAperson, and communication barrier experienced by counselor and PLWHA in VCT ClinicPuskesmas Dumai Kota.This research uses qualitative method, the subjects of informants selected usingpurposive technique, which become informant in this research are 5 people, that 1 counselorand 4 people living with HIV/AIDS (PLWHA). The data collection techniques used in thisresearch are observation, interviews, and documentation. Data analysis techniques byreducing data, collecting data, presenting data, drawing conclusions, and evaluation byusing tehniques of validity checking data that is triangulation.The results of this research are counseling procedures performed include pre-testcounseling and post-test counseling. The effectiveness of interpersonal communicationbetween counselors and PLWHA in VCT Clinic Puskesmas Dumai City has been runningeffectively, counselors and people living with HIV are equally open to each other; counselorsand PLWHA have high empathy with each other; positive behavior between counselor withPLWHA is shown by mutual understanding of condition of PLWHA and PLWHA receivinggood treatment from counselor; counselors and PLWHA support each other; the attitude ofequality between counselors and shown by the attitude of appreciation and mutual trust witheach other. Communication barriers felt by counselor during interpersonal communicationprocess between counselor and PLWHA in VCT Clinic Puskesmas Dumai City take placethat is psychological barrier and semantic barrier.